2008
DOI: 10.1086/529143
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Bacterial Load, Species Virulence, and Transfusion Reaction with Transfusion of Bacterially Contaminated Platelets

Abstract: Active surveillance detected 32-fold more bacterially contaminated platelet units and 10.6-fold more septic reactions than did passive surveillance, and virulent species and bacterial counts of > or =10(5) colony-forming units/mL were associated with more-severe transfusion reactions. Improved detection methods or use of pathogen inactivation technology are needed to eliminate this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
197
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(210 citation statements)
references
References 20 publications
11
197
1
1
Order By: Relevance
“…The not yet optimized detection limit of 10 4 live bacteria is close to what is shown to be relevant by Jacobs et al, (2008): "A detection method with a 10 3 colonyforming units/ml threshold would detect 90% of contaminants." Notably, up to 10 9 CFU have been found in expired platelet concentrates.…”
Section: Iccvam Recommendations For Future Mat Validation Studies Maymentioning
confidence: 70%
See 1 more Smart Citation
“…The not yet optimized detection limit of 10 4 live bacteria is close to what is shown to be relevant by Jacobs et al, (2008): "A detection method with a 10 3 colonyforming units/ml threshold would detect 90% of contaminants." Notably, up to 10 9 CFU have been found in expired platelet concentrates.…”
Section: Iccvam Recommendations For Future Mat Validation Studies Maymentioning
confidence: 70%
“…Recently, attention has focused on viral infections, although the incidence of HIV in blood products is less than 1 in 1,000,000 per unit (1 in 3,000 for bacterial contaminations) (Blajchman et al, 2005). Endotoxin determinations have been performed in some studies (Jacobs et al, 2008;Palavecino et al, 2010), but they are limited to Gram-negative infestations, which represent the minority of cases (e.g., out of 52 contaminated platelet concentrates reported by Jacobs et al, 2008, four were of Gram-negative origin), and do not allow determining cellbound pyrogens. Two large studies in France (BACTHEM study, Perez et al, 2001) and the USA (BaCon study, Kuehnert et al, 2001) revealed that platelets hold a significantly higher risk of bacterial contamination than erythrocyte concentrates, irrespective of their being single-donor or pooled preparations.…”
Section: Iccvam Recommendations For Future Mat Validation Studies Maymentioning
confidence: 99%
“…7 Active surveillance was performed by collecting 1-to 2-mL aliquots of apheresis or pooled platelet units at the time of issue for culture (see "Microbiology methods" below). Patients were evaluated for evidence of transfusion reactions as soon as positive culture results were obtained.…”
Section: Surveillance For Bacterial Contamination Of Platelet Units Amentioning
confidence: 99%
“…Investigation of transfusion reactions to platelets includes patient evaluation and Gram stain and culture of the remains of implicated platelet units. Patients' transfusion reactions, documented by active or passive surveillance, were classified by severity as previously described 7 and correlated with platelet and posttransfusion blood cultures and other investigations.…”
Section: Surveillance For Bacterial Contamination Of Platelet Units Amentioning
confidence: 99%
See 1 more Smart Citation